Strategies for microbiological contamination control in Api (Active Pharmaceutical Ingredients) and finished product Manufacturing: Compliance with USFDA guidelines (Journal of Advances and Scholarly Researches in Allied Education, 2025)
In many cases, the quality of the finished product depends on the microbiological properties of the medicinal components. Manufacturers are expected by the USFDA to quantify and describe the bioburden of their goods. This page describes the USFDA's and compendia's concerns over microbiological contamination. Also covered in this article are ways to identify microbial contamination, how to get rid of it, and where it comes from.